A NEW RECORD OF SEA SPIDER ENDEIS MOLLIS (CARPENTER, 1904) (FAMILY: PYCNOGONIDAE: WILSON, 1878) OFF THOOTHUKUDI, SOUTHEAST COAST OF INDIA (08º 35’ 22.5” N lat. 78º 27’ 40.9” E long and 08º 31’ 91.2”N lat. 78º 25’ 32.7”E) - T. Vaitheeswaran; T. Rajasekaran; S. Balasubramani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A new record of sea spider, Endeis mollis (Carpenter, 1904) off Thoothukudi coast of Gulf of Mannar, southeast coast of India is reported. Endeis mollis species was newly recorded from Thoothukudi coast of Gulf of Mannar, southeast coast of India. One specimen was caught at the depth of 310 m as an incidental by-catch. It was found in tropical waters from about 08º 35’ 22.5” N lat. 78º 27’ 40.9” E long and 08º 31’ 91.2”N lat. 78º 25’ 32.7”E/310 m from Thoothukudi fishing harbour, southeast coast of India.